Triple Mycobacterial ATP-synthase mutations impedes Bedaquiline binding: Atomistic and structural perspectives. (April 2020) - Salifu, Elliasu Y.; Agoni, Clement; Olotu, Fisayo A.; Soliman, Mahmoud E.S.
Graphical Abstract: Residue Interaction network analysis of mutant Mtb F1 F0 ATP synthase in complex with BDQ showcasing prominent residues network distortions. (A) Circled insert shows hotspot mutant residues (Val59A, Asp61B and Met66A). (B) Network and topology representation highlighting both hotspot residues with the corresponding interacting neighboring residues. (C) Closer network view showing the residual interaction network and centrality of the hotspot residues. Highlights: Effects of triple Mutants L59 V, E61D and I66 M on F1 F0 ATP-synthase of MTB towards the activity of Bedaquiline. Triple mutated structure of F1 F0 ATP-synthase was investigated across a 150 ns molecular dynamic simulation period. Mutation induces drastic reduction in BDQ binding affinity ( ΔG ) in the triple mutant protein due to a systemic loss in high-affinity interactions Mutation also induces a distortion of structural architecture of F1 F0 ATP-synthase in the presence of BDQ as revealed by the RIN and conformational analyses. Abstract: Bedaquiline (BDQ) has demonstrated formidable bactericidal activity towards Mycobacterium tuberculosis ( Mtb ) in the treatment of multi-drug resistant (MDR) and extensively drug resistant (XDR) tuberculosis (TB). BDQ elicits its therapeutic function by halting the ionic shuttle of Mtb via mycobacterial F1 F0 ATP-synthase blockade. However, triple mutations (L59 V, E61D and I66 M) at the ligand-binding cavity characterize emerging BDQ-resistant strains thereby restraining the potentials embedded in this anti-microbial compound, particularly in MDR/XDR-TB therapy. In this report, the effects of these triple mutations on BDQ- Mtb F1 F0 ATP-synthase binding were investigated using molecular dynamics, free energy binding and residue interaction network (RIN) analyses. The highlight of our findings is the drastic reduction in BDQ binding affinity ( ΔG ) in the triple mutant protein, which was caused by a systemic loss in high-affinity interactions primarily mediated by L59, E61 and I66. While wildtype L59 and I66 formed pi-alkyl interactions with BDQ at the F1 F0 ATP-synthase binding site, E61 elicited conventional (O--HO) bond. Upon transition, V59 and I66 were devoid of interactions with BDQ while D61 existed in a weaker non-conventional (C--HO) bond. Likewise, these mutations distorted the binding site and overall structural architecture of F1 F0 ATP-synthase in the presence of BDQ as revealed by the RIN and conformational analyses. Insights from this study could serve as a starting point for the structure-based design of novel inhibitors that could overcome mutational setbacks posed by BDQ-resistant strains in MDR/XDR-TB treatment.